Induction and maintenance of DNA methylation in plant promoter sequences by apple latent spherical virus-induced transcriptional gene silencing - Kon, Tatsuya; Yoshikawa, Nobuyuki (Frontiers in Microbiology, 2014)
Apple latent spherical virus (ALSV) is an efficient virus-induced gene silencing vector in functional genomics analyses of a broad range of plant species. Here, an Agrobacterium-mediated inoculation (agroinoculation) system was developed for the ALSV vector, and virus-induced transcriptional gene silencing (VITGS) is described in plants infected with the ALSV vector. The cDNAs of ALSV RNA1 and RNA2 were inserted between the CaMV 35S promoter and the NOS-T sequences in a binary vector pCAMBIA1300 to produce pCALSR1 and pCALSR2-XSB or pCALSR2-XSB/MN. When these vector constructs were agroinoculated into Nicotiana benthamiana plants with a construct expressing a viral silencing suppressor, the infection efficiency of the vectors was 100%. A recombinant ALSV vector carrying part of the 35S promoter sequence induced transcriptional gene silencing of the green fluorescent protein gene in a line of N. benthamiana plants, resulting in the disappearance of green fluorescence of infected plants. Bisulfite sequencing showed that cytosine residues at CG and CHG sites of the 35S promoter sequence were highly methylated in the silenced generation 0 plants infected with the ALSV carrying the promoter sequence as well as in progeny. The ALSV-mediated VITGS state was inherited by progeny for multiple generations. In addition, induction of VITGS of an endogenous gene (chalcone synthase-A) was demonstrated in petunia plants infected with an ALSV vector carrying the native promoter sequence. These results suggest that ALSV-based vectors can be applied to study DNA methylation in plant genomes, and provide a useful tool for plant breeding via epigenetic modification.